Hero of Contemporary Russian Prose: Anna Skotnicka, Szczelina. Bohater współczesnej prozy rosyjskiej i jego światy, Wydawnictwo Uniwersytetu Jagiellońskiego, Kraków 2020, 335 s. ISBN: 978-83-233-4771-2 - Tyszkowska-Kasprzak, Elżbieta (Slavica, 2023)
The text contains a review of the monograph by the Polish literary critic Anna Skotniсka A fissure: A hero of contemporary Russian prose and his worlds. The author considers incompleteness, absence, and insufficiency as a property of the existence of the character of the works of Russian writers of the late 20th to early 21st centuries. The sources of this problem, according to Skotnicka, can be seen in the state of disintegration of the social, psychological and mental image of the world in a changing reality, especially historical changes: the collapse of the Soviet Union, as well as political, cultural and social transformations. With these phenomena, the Polish literary critic also connects the concept of chaos, which is characteristic of the postmodern perception of the world as disunited, incomprehensible, alien in relation to people. Skotniсka considers these problems based on the works of Mikhail Kuraev, Svetlana Aleksievich, Roman Senchin, Lyudmila Petrushevskaya, Lyudmila Ulitskaya, Vladimir Makanin, and Mikhail Shishkin. The author refers to the current achievements of the humanities, especially philosophy. The work is innovative and stimulates reflection on the state of the modern human.